The impact of the italian law mandating an automatic external defibrillation in all sports venues on sudden cardiac arrest survival. (11th May 2022) - Gianni, A; Villa, G; Mattesi, G; Botteri, M; Corrado, D; Zorzi, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The chances of surviving a sport-related cardiac arrest depend strictly on resuscitation efforts. Since 2015, all Italian recreational and competitive sport venues must be equipped with automated external defibrillators (AEDs), and trained staff must be present during competitions. The aim of the study was to evaluate the incidence and survival rates of cardiac arrests in sport Venues in the Lombardia region of Italy before and after 2015. Methods: We collected retrospectively data regarding all sudden cardiac arrests of presumed cardiac origin that involved both athletes and non-athletes (coaches, referees, spectators, etc.) and which occurred in sports venues of the Lombardia region in the period 2015-2019 versus those that occurred in the period 2011-2014, when automatic external defibrillators were not mandatory yet. All cases have been gathered thanks to the database built by the regional territorial emergency service (AREU) of the Lombardia region and consulting the news reported by the local and national press. Results: Between 2015 and 2019, the incidence of cardiac arrest of presumed cardiac origin which affected athletes in sports venues of the Lombardia region was 0.19 per 100, 000 inhabitants/year, versus 0.28 per 100, 000 inhabitants/year in the period 2011-2014 (p<0.005). The average age of the victims was 49.9 years in 2015-2019 and 52 years in 2011-2014 (p=0.96). After the enactment of the "compulsory AED law", the proportion of cardiac arrests treated with onsite AEDs increased from 15% to 42.1% (p<0.001) and the return of spontaneous circulation (successful resuscitation) increased from 67% to 80% (p<0.05). The association between mandatory presence of AEDs in sports venues and resuscitation success in terms of ROSC was found significant (p<0.05). Conclusions: Cardiac arrest in sports venues is a rare event and involves mainly male athletes older than 30 years old. A nationwide law mandating the presence of AEDs in all sport venues significantly increased the proportion of individuals suffering cardiac arrest who received defibrillation before the emergency medical system arrival and favorably influenced survival rates.